Theorising the Idea of Aesthetic Self in Abhinavagupta - Baghel, Virosh Singh (Integrated Journal for Research in Arts and Humanities, 2024)
The paper examines Abhinavagupta’s concept of rasa, or aesthetic experience, and attempts to theorise the idea of an aesthetic self. According to him, while experiencing a drama (nāṭya), spectators attain a collective state of consciousness when they resonate with the underlying poetic intention and experience generalised emotions (through sādhāraṇīkaraṇa), creating a uniformity (ekaghanatā) among them, de-contextualising them from their personal-causal relations. Subsequently, their consciousness merges into a collective whole, becoming a universal subject that experiences generalised emotions during an aesthetic experience. However, this subject does not attain the status of the universal self because, according to Abhinavagupta, while aesthetic experience (rasāsvāda) resembles spiritual experience (brahmāsvāda) and leads to self-dissolution, it is not a complete dissolution as it remains influenced by the phenomenological realities of life. However, when spectators reach the highest level of aesthetic experience, they relish śānta rasa, where they experience an undifferentiated bliss (ānandaikaghana). This bliss is the natural state of mind, where the enjoyment leads to the sinking of mental activities (cittavṛttis) into the subconscious, resulting in the experience of one’s consciousness or self. Nonetheless, since aesthetic experience does not result in total self-dissolution, the paper argues that although collective consciousness forms a universal subject, an ‘Impersonalised’ dimension of the self remains. This dimension is neither fully detached from the world nor entirely dissolved into the self. The paper concludes that this Impersonalised self, which bears the collective experience of generalised emotions in an aesthetic experience, can be referred to as the ‘aesthetic self.’